2007
DOI: 10.1111/j.1471-4159.2007.04484.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐induced changes in epinephrine expression in the adrenal medulla in vivo

Abstract: Immobilization (IMMO) stress was used to examine how stress alters the stress hormone epinephrine (EPI) in the adrenal medulla in vivo. In rats subjected to IMMO for 30 or 120 min, adrenal corticosterone increased to the same extent. In contrast, EPI changed very little, suggesting that EPI synthesis replenishes adrenal pools and sustains circulating levels for the heightened alertness and physiological responses of the 'flight or fight' response. In part, stress activates EPI via the phenylethanolamine N-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
37
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 47 publications
4
37
0
3
Order By: Relevance
“…GCs are key regulators of PNMT, and we have previously demonstrated that the induction of PNMT gene expression in vitro upon GC administration is mediated by GC response elements (GRE) within the PNMT promoter . Further, altered activity of the transcription factors regulate PNMT not only in vitro (Tai et al , 2010a, but also in immobilization stress (Tai et al 2007, Wong et al 2008 as well as in a genetic model of hypertension, the SHR (Nguyen et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…GCs are key regulators of PNMT, and we have previously demonstrated that the induction of PNMT gene expression in vitro upon GC administration is mediated by GC response elements (GRE) within the PNMT promoter . Further, altered activity of the transcription factors regulate PNMT not only in vitro (Tai et al , 2010a, but also in immobilization stress (Tai et al 2007, Wong et al 2008 as well as in a genetic model of hypertension, the SHR (Nguyen et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This activation increases the release of catecholamines and the release of co-located substances, including neuropeptides at the sympathetic neuroeffector juncture into the blood. For a number of years, it has been known that stress induces a cascade of adaptive neuroendocrine responses, which generally includes the synthesis and release of Cor and EPI from the adrenal gland (44,45). Melin et al showed that when rats were exposed to heat stress followed by exhaustive exercise, the levels of EPI and norepinephrine were increased (46).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that stresses induce the release of epinephrine into the circulation and elevate blood pressure, 5,23,24 indicating a psychophysiological link between stress, adrenomedullary activation, and hypertension. 25 We demonstrated that the arteries from LPAR1-deficient mice became less responsive to phenylephrine stimulation in contraction, Two hundred seventy-eight healthy individuals were randomly recruited, and rs531001 was genotyped by direct sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we demonstrated that mice lacking the LPAR1 gene presented an attenuated response to sleep deprivation-induced blood pressure elevation and phenylephrine-induced vasoconstriction, dependent on the dosages of LPAR1 gene. These genetic and functional evidences suggest that LPAR1 is an EH susceptibility gene.Previously, it has been shown that stresses induce the release of epinephrine into the circulation and elevate blood pressure, 5,23,24 indicating a psychophysiological link between stress, adrenomedullary activation, and hypertension. 25 We demonstrated that the arteries from LPAR1-deficient mice became less responsive to phenylephrine stimulation in contraction, Figure 2.…”
mentioning
confidence: 99%